SINGLE MOLECULE BIOPHYSICS: OPTICAL TWEEZERS FOR STUDYING DNA PROTEIN INTERACTIONS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Single molecule biophysics has transformed molecular biology by enabling direct visualization and mechanical manipulation of individual biomolecular events. Among single molecule techniques, optical tweezers stand out for their ability to apply precise piconewton level forces and nanometer scale displacements, making them uniquely suited to probing the dynamics of DNA protein interactions. These interactions underpin fundamental processes such as replication, transcription, repair, and chromatin remodeling. Recent methodological advances, including force–fluorescence integration, real time tracking, and high precision calibration, have expanded capabilities to measure protein binding kinetics, mechanical stability of nucleoprotein complexes, and the effects of tension on regulatory mechanisms. This review integrates contemporary developments in optical tweezer methodology, highlights key experimental findings on DNA protein complexes, discusses computational and analytical frameworks, and addresses current limitations and future directions. The ongoing integration of optical tweezers with advanced microscopy and machine learning analysis promises deeper mechanistic insight into how proteins interact with and modulate DNA at the single molecule level.